CUSTOMER SATISFACTION SELECTED CELLULAR SERVICES PROVIDERS IN VILLUPURAM DISTRICT - KANAGARAJU, Dr.P.; KARTHIKEYAN, R. (The journal of contemporary issues in business and government, 2021)
Customer satisfaction is a term frequently used in marketing. It is a measure of how products and services supplied by a company meet or surpass customer expectation. Customer satisfaction, this study is aimed to analysis the customer satisfaction in villupuram district, how the people choosing the brand of cellular phone and what are the parameter to choose the selected brands. Brand preference reflects a desire to use a particular company’s products or services, even when there are equally priced and equally-available alternatives. In fact, more often than not, brand preference indicates a desire to seek out a specific product or service, even when it requires paying more or expending more effort to obtain it. Brand preferences are important to companies because it provides an indicator of their customers’ loyalty, the success of their marketing tactics, and the strength of their respective brands. Measure of brand loyalty in which a consumer will choose a particular brand in presence of competing brands, but will accept substitutes if that brand is not available. Brand preference is strongly linked to brand choice that can influence the consumer decision making and activate brand purchase, many brands